Androgen-Induced Rhox Homeobox Genes Modulate the Expression of AR-Regulated Genes - Hu, Zhiying (The Endocrine Society, 2010)
Rhox5, the founding member of the reproductive homeobox on the X chromosome (Rhox) gene cluster, encodes a homeodomain-containing transcription factor that is selectively expressed in Sertoli cells, where it promotes the survival of male germ cells. To identify Rhox5-regulated genes, we generated 15P-1 Sertoli cell clones expressing physiological levels of Rhox5 from a stably transfected expression vector. Microarray analysis identified many genes altered in expression in response to Rhox5, including those encoding proteins controlling cell cycle regulation, apoptosis, metabolism, and cell-cell interactions. Fifteen of these Rhox5-regulated genes were chosen for further analysis. Analysis of Rhox5-null male mice indicated that at least nine of these are Rhox5-regulated in the testes in vivo. Many of them have distinct postnatal expression patterns and are regulated by Rhox5 at different postnatal time points. Most of them are expressed in Sertoli cells, indicating that they are candidates to be directly regulated by Rhox5. Transfection analysis with expression vectors encoding different mouse and human Rhox family members revealed that the regulatory response of a subset of these Rhox5-regulated genes is both conserved and redundant. Given that Rhox5 depends on androgen receptor (AR) for expression in Sertoli cells, we examined whether some Rhox5-regulated genes are also regulated by AR. We provide several lines of evidence that this is the case, leading us to propose that RHOX5 serves as a key intermediate transcription factor that directs some of the actions of AR in the testes.